(untitled) (Nigerian Journal of Physiological Sciences, 2024)
Cadmium, despite being an environmental pollutant has a wide range of applications and causes oxidative damage to the testes and impairment of male reproductive function. PurXcel, a polyherbal remedy is said to be rich in antioxidants and improves fertility. But there are no scientific records of its effect on Cadmium-induced male reproductive impairment, hence this study. Twenty male wistar rats were randomly assigned into 4 groups of 5 rats each namely control, Cadmium-only, PurXcel-only and Cadnium+PurXcel groups. Treatment with PurXcel lasted for 28 days after which blood samples were collected and testes and epididymis harvested for evaluation of relevant parameters. Body weight changes (BWC) as well as weights of testes and epididymis were significantly reduced in Cadmium-only group (P<0.05 each) compared with the control. PurXcel given alone and in combination with Cadmium significantly increased (P<0.05) the BWC as well as testicular and epididymal weights in comparison with the Cadmium-only group. Sperm function indices (count, motility, viability and normal morphology) and reproductive hormones (GnRH, FSH, LH and testosterone) activities were significantly decreased (P<0.05) in the Cadmium-only group compared with the control but higher in all treated groups (P<0.05) compared with Cadmium-only group. Testicular activities of MDA and TBARS were significantly increased in the Cadmium-only group compared with control (P< 0.05) but reduced in treated groups (P< 0.05) compared with Cadmium–only group. The activities of testicular SOD, GPx and Catalase as well as total antioxidant capacity were significantly reduced in the Cadmium-only group compared with control (P<0.05) but increased in the treated groups compared with Cadmium-only group (P<0. Testicular morphometric parameters showed decreases in Sertoli cell count, Leydig cell count, Johnson’s score, seminiferous tubules diameter and germinal epithelial height (P<0.05) in the Cadmium-only group compared with the control but which were significantly higher in the Cadmium+PurXcel than in the Cadmium-only groups (P<0.05). A section of the testes also revealed mainly empty luminal cavities and scanty intervening interstitium in the Cadmium-only group compared with the control. The PurXcel–only and Cadmium+PurXcel groups, have dense intervening interstitium and luminal cavities filled with mature sperm cells. There were loosely packed epididymis and which were mainly empty in the Cadmium-only group whereas the epididymis of the PurXcel-only and Cadmium+PurXcel groups have a densely packed epididymis filled with spermatozoa. We conclude that PurXcel improves Cadmium-induced male reproductive toxicity and given alone, improves testicular antioxidant status in Wistar Rats.